Two cases of kidney transplantation‐associated thrombotic microangiopathy successfully treated with eculizumab. (July 2016) - Ikeda, Takashi; Okumi, Masayoshi; Unagami, Kohei; Kanzawa, Taichi; Sawada, Anri; Kawanishi, Kunio; Omoto, Kazuya; Ishida, Hideki; Tanabe, Kazunari
Abstract: Transplantation‐associated thrombotic microangiopathy (TA‐TMA) is relatively rare and requires immediate intervention to avoid irreversible organ damage or death; however, consensus regarding the treatment approach is lacking. Atypical haemolytic uraemic syndrome (aHUS) is a rare disease caused by dysregulation of the alternative complement pathway resulting in TMA. aHUS is histologically similar to TA‐TMA; approximately 60% of TA‐TMA patients have complement dysregulation. Eculizumab, a humanized anti‐C5 monoclonal antibody, inhibits terminal membrane‐attack complex formation and TMA progression. Eculizumab has been successfully used to treat aHUS post‐transplant. We present two cases of kidney TA‐TMA due to unknown causes, suspected antibody‐mediated rejection, or calcineurin inhibitor (CNI)‐related toxicity that developed on day 1 or 2 post‐kidney transplantation. Low platelet count and haemoglobin level with red cell fragments were detected. Despite steroid pulse, plasma exchange (PE), and intravenous immunoglobulin therapy, TA‐TMA did not improve; therefore, eculizumab was administered despite no genetic testing. Laboratory data, including renal function, improved immediately. TA‐TMA treatment primarily involves PE initiation or CNI discontinuation; eculizumab can be used to safely treat TA‐TMA and then be ceased in the short term. Therefore, eculizumab administration might be beneficial for kidney TA‐TMA as early as the diagnosis of refractory to PE.